Woman becoming… Gender possibilities in selected speculative short stories of Intan Paramaditha and Isabel Yap - Chin, Grace V.S. (UI Scholars Hub, 2023)
The ontological question of woman’s nature forms the focus of this essay, which develops the theory of “woman-becoming…” to examine how the hegemonic patriarchal discourses and constructs of woman and femininity are subverted and reinterpreted in two speculative short stories by transnational Southeast Asian women writers, namely Intan Paramaditha’s “Beauty and the Seventh Dwarf” (2018) and Isabel Yap’s “Good Girls” (2021). Of interest here are the gender possibilities of the female characters, which uphold women’s freedom, agency, thinking, feeling, creation, narration and expression in the making of herstory—indeed, everywoman’s potential for change and transformation, and to become more than what society expects and demands from woman. Materialized through the resistant and rebellious multitudinous female self and body, woman’s becoming and her gender possibilities ultimately interrogate, vex and unsettle the entrenched sociocultural and politicized meanings, representations and stereotypes of woman’s nature in the Southeast Asian context.